Caste polymorphism of apterous line of the Neotropical termite Nasutitermes corniger (Motschulsky) (Isoptera, Termitidae) - Lima,Victor Luiz de Souza (2013)
Termite societies are structured by individuals that can be grouped into castes and instars. The development of these instars in most species occurs in irregular patterns and sometimes is distinguished subcastes in physical systems that originate polymorphic soldiers and workers. In this study, we characterized the morphological diversity of castes of apterous in Nasutitermes corniger. We collected four colonies of N. corniger, one every three months between May 2011 and February 2012. Individuals of the nest were separated into groups: larval stages, workers and presoldiers and soldiers. A morphometric analysis was performed on individuals from each group based on head width, metatibia, antenna, and thorax length. The data were submitted to discriminant analysis to confirm different morphological types inside these groups. The apterous line of N. corniger is composed of one first larval instar and two second larval instar. The workers caste has two lines of development with four instars in a larger line and three instars in a lower line. Two morphological types were identified in presoldiers and soldiers. The pattern of castes was similar to other species of the genus, in which bifurcation into two lines of workers, one smaller and one larger occurs after the first molt.